AB0635 POTENTIAL BIOMARKERS OF SKIN CHANGES IN SYSTEMIC SCLEROSIS. (June 2019) - Bečvář, Radim; Štorkánová, Hana; Šumová, Barbora; Špiritović, Maja; Oreska, Sabina; Šenolt, Ladislav; Tomčík, Michal
Abstract : Background: Skin fibrosis is a hallmark of systemic sclerosis (SSc). There are no widely accepted biomarkers of skin involvement in this condition. Several serum or plasma markers have been studied in patients with SSc - monocyte chemoattractant protein-1 (MCP-1), chemokine (C-X-C motif) ligand 8 (CXCL8), interleukin-13 (IL-13), and some more recognized such as - platelet derived growth factor (PDGF), transforming growth factor-beta 1 (TGF-beta 1), epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF). Objectives: The aim of this study was to assess several circulating biomarkers which may be relevant to the fibrosing process and further to correlate the obtained data with clinical indicators specific for SSc skin involvement. Methods: 59 SSc patients (M/F 9/50; mean age 52.1 years, mean disease duration 6.7 years, 36 patients with limited cutaneous SSc and 23 with diffuse cutaneous SSc. As a control group 36 healthy individuals matched to sex and age were examined. Serum concentrations of bFGF, granulocyte-colony stimulating factor (G-CSF), granulocyte-macrophage-colony stimulating factor (GM-CSF), MCP-1, PDGF, IL-8 and 13 were analysed using commercial multiplex kit. The following clinical examinations were performed: modified Rodnan skin score (mRSS), Hand Mobility in Scleroderma Test (assessing hand function) (HAMIS), Cochin Hand Function Scale (hand function) (CHFS), Delta Finger-to-Palm Distance (extension-flexion) (dFTP), inter-lip Distance (inter-lip), inter-incisor Distance (inter-incisor), and Mouth Handicap in Systemic Sclerosis Scale (mouth opening) (MHISS). For statistical evaluation Spearman's correlation coefficient was used. Results: When compared with healthy controls serum concentrations of bFGF (p<0.001), G-CSF (p<0.0001), GM-CSF (p<0.0001), MCP-1 (p<0.0001) IL-8 (p<0.0001), and IL-13 (p<0.001) were significantly elevated in SSc cohort. PDGF levels were increased in SSc patients with only a lower significance (p<0.01). bFGF, G-CSF, MCP-1 and IL-8 levels correlated significantly (p<0.05) with mRSS and HAMIS. GM-CSF levels correlated with mRSS and HAMIS and there was only a trend for negative correlation with inter-incisor. The was no correlation of IL-13 and PDGF levels with the evaluated clinical data. Conclusion: Our results have shown that G-CSF, GM-CSF and IL-8 play a substantial role in SSc fibrosing process. Potential biomarkers as bFGF, G-CSF, MCP-1 and IL-8 correlated with a few clinical indices of SSc skin involvement. References: [1] Carulli MT, Handler C, Coghlan JG, Black CM, Denton CP. Can CCL2 serum levels be used in risk stratification or to monitor treatment response in systemic sclerosis?Ann Rheum Dis2008;67:105-9. [2] Chujo S, Shirasaki F, Kondo-Miyazaki M, Ikawa Y, Takehara K. Role of connective tissue growth factor and its interaction with basic fibroblast growth factor and macrophage chemoattractant protein-1 in skin fibrosis. J Cell Physiol2009;220:189-95. [3] Fuschiotti P, Larregina aT, Ho J, Feghali-Bostwick C, Medsger TA Jr. Interleukin-13-producing CD8+ T cells mediate dermal fibrosis in patients with systemic sclerosis. Arthritis Rheum2013;65:236-46. [4] Hasegawa M, Fujimoto M, Matsushita T, et al. Serum chemokine and cytokine levels as indicators of disease activity in patients with systemic sclerosis. Clin Rheumatol2011;30:231-7. Acknowledgement: This study was supported by research grants aZV 16-33574A and aZV 16-33542A. Disclosure of interests: Radim Bečvář Consultant for: consultancy actelion, Hana Štorkánová: None declared, Barbora Šumová: None declared, Maja Špiritović: None declared, Sabina Oreska: None declared, Ladislav Šenolt Grant/research support from: abbVie, Consultant for: abbVie, Bristol-Myers Squibb, Celgene Corporation, Merck Sharp and Dohme, Novartis, Pfizer, Roche, UCB, amgen, Takeda, Speakers bureau: abbVie, amgen, Bristol-Myers Squibb, Celgene Corporation, Eli Lilly, Merck Sharp and Dohme, Novartis, Pfizer, Roche, UCB, Michal Tomčík: None declared